X-Ray Results During the Introduction of Osteoplastic Materials for The Prevention of Atrophy of the Alveolar Process (Eurasian Research Bulletin, 2023)
The aim of the research is to determine the indications for reconstruction of the alveolar process after tooth extraction according to orthodontic indications.